2016
DOI: 10.3892/ol.2016.5172
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-199a-5p inhibits cisplatin-induced drug resistance via inhibition of autophagy in osteosarcoma cells

Abstract: Abstract. Osteosarcoma (OS) is the most common cancer of the bone. Chemotherapy is commonly used for the clinical treatment of OS. However, chemoresistance to cisplatin [also known as diamminedichloridoplatinum (II) (DDP)] is a major obstacle for OS therapy, the underlying mechanism of which is not fully understood. The present study aimed to investigate the role of microRNA (miR)-199a-5p in the regulation of chemoresistance to DDP in OS cells. Reverse transcription-quantitative polymerase chain reaction demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 26 publications
2
43
2
1
Order By: Relevance
“…miR-199a suppressed autophagy by GSK3Ī²/mTOR complex signaling [22]. Moreover, miR-199a directly targeted Beclin1 to inhibited autophagy and reversed drug resistance induced by cisplatin of osteosarcoma cells [23]. Our results also demonstrated that miR-199a targetly regulated Beclin1, which was consistent with the previous study.…”
Section: Discussionsupporting
confidence: 91%
“…miR-199a suppressed autophagy by GSK3Ī²/mTOR complex signaling [22]. Moreover, miR-199a directly targeted Beclin1 to inhibited autophagy and reversed drug resistance induced by cisplatin of osteosarcoma cells [23]. Our results also demonstrated that miR-199a targetly regulated Beclin1, which was consistent with the previous study.…”
Section: Discussionsupporting
confidence: 91%
“…Cisplatin induced autophagy in a concentration-dependent manner in the examined cells, as demonstrated by the western blot results for the autophagy markers LC3-I, LC3-II and p62. This compound has previously been demonstrated to induce autophagy in various types of cancer cells, such as ovarian cancer cells and osteosarcoma cancer cells (35,36), and another study indicated that autophagy serves a protective role in cisplatin resistance (34). The results of the present study demonstrated that the blockade of autophagy promoted cisplatin-induced cell death in SKOV3 and SKOV3/DDP cells, and partially re-sensitized cisplatin-resistant SKOV3/DDP cells.…”
Section: Discussionsupporting
confidence: 69%
“…Intrinsic or acquired MDR is one of the main reasons for chemotherapy failure, leading to the recurrence of malignant tumors and ultimately, patient relapse or death [ 3 ]. Various mechanisms have been attributed to MDR, such as enhanced drug efflux, increased DNA damage repair, reduced apoptosis, elevated autophagy, and/or altered drug metabolism [ 2 , 4 ā€“ 6 ]. In order to improve the efficacy of chemotherapy, strategies to reverse MDR have been studied extensively over the past few decades.…”
Section: Introductionmentioning
confidence: 99%